Collective action, premodern good government, and the transformation from subaltern to politically engaged citizenry - Blanton, Richard E.; Fargher-Navarro, Lane F. (Frontiers in Human Dynamics, 2024)
Research inspired by collective action theory has provoked a rethinking of premodern governance, including state formation. We briefly summarize key elements of this theoretical turn, first, by demonstrating that, as predicted by the existing theory, political collective action is enhanced when the provision of good government motivates taxpayer compliance. Beyond that key process, our cross-cultural comparative investigation identified a suite of corollary social and cultural factors, including civic ritual, that, side-by-side with good government, served to undergird the institution of political collective action. We investigate, in particular, policies and practices that fostered the transformation of what had been a dominated and socially fragmented subaltern into a politically engaged and conditionally compliant citizenry. We discuss this process in relation to administrative policies and practices and in relation to evidence we found for directed cultural change purposed to enhance consensus and forbearance in the face of social divisiveness and political inequality.1 Cross-cultural comparative analysis has a long history of methodological development; a readable introduction is Ember and Ember (2001).